Profile of atrial fibrillation inpatients: Cardiovascular risk factors and cardiac rehabilitation programme delivery and referral patterns. Issue 6 (13th October 2014) - Gallagher, Robyn; Zhang, Ling; Roach, Kellie; Sadler, Leonie; Belshaw, Julie; Kirkness, Ann; Proctor, Ross; Neubeck, Lis
Abstract : Atrial fibrillation (AF) is increasingly common; however, the cardiovascular risk factor profile and the patterns of delivery and referral to cardiac rehabilitation (CR) in this population are poorly described. We conducted an audit of medical records ( n = 145) of patients admitted with AF in one local health district in Sydney, Australia. Patients were aged a mean 72 years, and 51% were male. Lack of risk factor documentation was common. Despite this, 65% had two or more modifiable cardiovascular risk factors, including hypertension (63%) and hypercholesterolaemia (52%). Referral to Phase II CR occurred for 25% and was decreased with permanent AF diagnosis and increased with more risk factors. AF patients admitted to hospital have multiple cardiovascular risk factors but limited risk factor screening and/or referral to outpatient CR programmes.